A STUDY ON LEARNING STRATEGIES USED BY SECOND- SEMESTER ENGLISH STUDY PROGRAMS IN INTERMEDIATE READING AND WRITING FKIP UNRI - Geladis Afira; Mahdum; Muhammad Syarfi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the learning strategies used by second-semester students in the English Education Study Program during reading and writing activities in the Intermediate Reading and Writing course. Employing a quantitative descriptive design, the study involved 117 students selected through simple random sampling. Data were collected using a Likert-scale questionnaire covering metacognitive, cognitive, and socioaffective strategies based on O’Malley and Chamot’s (1990) classification. The findings reveal that all three strategy categories were used at a high level, with socioaffective strategies being the most dominant, followed by metacognitive and cognitive strategies. Students showed strong help-seeking behavior and active monitoring of comprehension, yet demonstrated weaknesses in planning, peer feedback, and applying new grammar structures in their writing. These results suggest that students rely more on social support and vocabulary-based strategies rather than planning and grammar-oriented approaches, indicating the need for instructional practices that promote more balanced and autonomous learning.